You are only mine: Engage with voice assistant while find destinations and accommodations - Ferreira, Mónica Mendes; Loureiro, S. M. C.; Pereira, H. (Journal of Promotion Management, 2022)
In a changing world, where artificial intelligent devices are communicating with consumers, understand the communication interaction between firms and consumers is key to the success of business. The current study aims to analyze the consumer-virtual assistant communication by demonstrating the effect of authenticity and attachment as drivers of engagement via psychological ownership. A panel sample of 170 users of voice assistants were recruited to fulfill a survey using Qualtrics. Findings show that when users view their communication with virtual assistants as authentic, they become engaged. Yet, the strength of the relationship between attachment and engagement tends to be higher than the relationship between authentic and engagement. Prominence is more important in creating attachment then self-connection. Therefore, consumers who are closer to their virtual assistant, thinking, feeling, and using the device to interact with firms and brands are also more related to the information and recommendations given by the device and stablish a stronger interaction.